Activimeter “in situ” calibration methodology to 111In and 123I (Brazilian Journal of Radiation Sciences (BJRS), 2023)
The activimeter calibration has the purpose of ensure greater reliability in measurement results, hence the activimeters used are commonly installed in controlled areas and, in some cases, with difficult access. The activimeter “in situ” calibration methodology presented in this work allows its execution only with the displacement of the radioactive samples and not of the activimeter itself, which simplifies the procedure of nuclear medicine services and at radiopharmaceuticals production centers, without affecting the quality and accuracy of measurements. After the application of the methodology by qualified technicians, the obtained results of the tested activimeters showed its importance since the calibration factors can present correction of up to 5% for 111In and greater than 5% for 123I.